Mechanisms in endocrinology: diabetic cardiomyopathy: pathophysiology and potential metabolic interventions state of the art review - Levelt, E; Gulsin, G; Neubauer, S; McCann, G (BioScientifica, 2018)
Heart failure is a major cause of morbidity and mortality in type 2 diabetes. Type 2 diabetes contributes to the development of heart failure through a variety of mechanisms, including disease-specific myocardial structural, functional and metabolic changes. This review will focus on the contemporary contributions of state of the art non-invasive technologies to our understanding of diabetic cardiomyopathy, including data on cardiac disease phenotype, cardiac energy metabolism and energetic deficiency, ectopic and visceral adiposity, diabetic liver disease, metabolic modulation strategies and cardiovascular outcomes with new classes of glucose-lowering therapies.